2021
DOI: 10.3389/fimmu.2021.612271
|View full text |Cite
|
Sign up to set email alerts
|

Stroma Involvement in Pancreatic Ductal Adenocarcinoma: An Overview Focusing on Extracellular Matrix Proteins

Abstract: Pancreatic cancer is the seventh leading cause of cancer-related deaths worldwide and is predicted to become second in 2030 in industrialized countries if no therapeutic progress is made. Among the different types of pancreatic cancers, Pancreatic Ductal Adenocarcinoma (PDAC) is by far the most represented one with an occurrence of more than 90%. This specific cancer is a devastating malignancy with an extremely poor prognosis, as shown by the 5-years survival rate of 2–9%, ranking firmly last amongst all canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(72 citation statements)
references
References 134 publications
1
47
0
Order By: Relevance
“…Rhim et al reported that some components of the tumor stroma act to restrain tumor growth, and the reduction of stromal content by sonic hedgehog gene deletion led to the emergence of more aggressive tumors that exhibited undifferentiated histology, increased vascularity, and heightened proliferation (50). In addition, Liot et al also demonstrated that the TME contains anti-tumor components (51). Although it is well known that the Wnt signaling pathway promotes tumor progression (52, 53), Green et al proved that Wnt3a derived from CAFs can both promote and inhibit the growth of breast tumors (54).…”
Section: Diversity Of Caf Functionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rhim et al reported that some components of the tumor stroma act to restrain tumor growth, and the reduction of stromal content by sonic hedgehog gene deletion led to the emergence of more aggressive tumors that exhibited undifferentiated histology, increased vascularity, and heightened proliferation (50). In addition, Liot et al also demonstrated that the TME contains anti-tumor components (51). Although it is well known that the Wnt signaling pathway promotes tumor progression (52, 53), Green et al proved that Wnt3a derived from CAFs can both promote and inhibit the growth of breast tumors (54).…”
Section: Diversity Of Caf Functionsmentioning
confidence: 99%
“…In addition, Liot et al. also demonstrated that the TME contains anti-tumor components ( 51 ). Although it is well known that the Wnt signaling pathway promotes tumor progression ( 52 , 53 ), Green et al.…”
Section: Origin and Heterogeneity Of Cafsmentioning
confidence: 99%
“…There is an urgent need to identify more potential targets for drugs and biomarkers for early diagnosis [20][21][22]. ECM is a fundamental and important component of all tissue organs and has been found to interact with tumor cells and regulate tumor growth, proliferation, differentiation, adhesion and metastasis [23][24][25]. Here, we con rmed that most of the Core-ECM genes like Collagens, Proteoglycans and Glycoproteins were high expressed in LSCC compared with adjacent normal mucosa tissues (Figure S2).…”
Section: Discussionmentioning
confidence: 99%
“…This dense environment changes cellular properties, and it has been suggested that desmoplasia is a cause of the chemoresistance of pancreatic cancer (Whatcott et al, 2012). The role of the ECM in PDACstromal interactions was recently reviewed (Liot et al, 2021).…”
Section: Insights Into Pancreatic Cancermentioning
confidence: 99%